A carboxymethylcellulose-mediated aqueous colloidal process for building plasmonic–excitonic supramolecular nanoarchitectures based on gold nanoparticles/ZnS quantum emitters for cancer theranostics. Issue 20 (5th October 2021) - Caires, Anderson J.; Mansur, Herman S.; Mansur, Alexandra A. P.; Carvalho, Isadora C.; Carvalho, Sandhra C.
Abstract : A carboxymethylcellulose-mediated aqueous colloidal process for building plasmonic–excitonic supramolecular nanoarchitectures: "nanoweapons" to fight against cancer. Abstract : Despite indisputable advances in recent years, glioblastoma multiforme (GBM) remains one of the most lethal types of brain cancers. Hybrid matter-based nanostructures have exceptional potential as a multimodal tool against GBM by amalgamating the earliest possible diagnosis with options of therapy termed nanotheranostics . Thus, in this research, we report for the first time the rational design and synthesis of novel plasmonic–excitonic nanohybrids produced based on a green nanomedicine approach using a carboxymethylcellulose (CMC) multifunctional biopolymer acting simultaneously as a capping ligand and biocompatible shell through an eco-friendly aqueous colloidal process for nanotheranostics of brain cancer cells. These nanohybrids comprised of gold nanoparticles (AuNPs) coupled to a layer of ZnS semiconductor quantum emitter (ZnS-QE) surrounded by the CMC macromolecular shell (AuNP-ZnS@CMC), which displayed water-dispersed colloidal supramolecular nanoarchitectures stabilized by the polysaccharide chemical functional groups. They demonstrated nanotheranostic behavior by concurrently integrating the excitonic activity of the ZnS-QE layer for fluorescence bioimaging with the plasmonic properties of AuNPs for effectively killing GBM cancer cells in vitro . Hence, it can be anticipated that this hybrid nanoplatform could pave the way for the development of advanced multifunctional green nanomedicine against cancer through an environmentally sustainable strategy.